Potential Contribution of Biotechnology to Agricultural Production in the West Asia and North Africa Region - Weigand, F.; Baum, M. (International Service for National Agricultural Research, 2001)
The purpose of this paper is to shed light on how we can estimate the potential contribution of biotechnology to agricultural production in the West Asia and North Africa region with respect to the ICARDA-mandated crops. The attempt is made by describing ICARDA’s experience over the last decade.